Automation of intracoronary continuous thermodilution for absolute coronary flow and microvascular resistance measurements. Issue 2 (20th June 2022) - Candreva, Alessandro; Gallinoro, Emanuele; Fernandez Peregrina, Estefania; Sonck, Jeroen; Keulards, Danielle C. J.; van't Veer, Marcel; Mizukami, Takuya; Pijls, Nico H. J.; Collet, Carlos; De Bruyne, Bernard
Abstract: Aim: Microvascular resistance reserve (MRR) as derived from continuous intracoronary thermodilution specifically quantifies microvasculature function. As originally described, the technique necessitates reinstrumentation of the artery and manual reprogramming of the infusion pump when performing resting and hyperemic measurements. To simplify and to render this procedure operator‐independent, we developed a fully automated method. The aim of the present study is to validate the automated procedure against the originally described one. Methods and Results: For the automated procedure, an infusion pump was preprogrammed to allow paired resting‐hyperemic thermodilution assessment without interruption. To validate the accuracy of this new approach, 20 automated measurements were compared to those obtained in the same vessels with conventional paired resting‐hyperemic thermodilution measurements (i.e., with a sensor pullback at each infusion rate and manual reprogramming of the infusion pump).  A close correlation between the conventional and the automated measuring technique was found for resting flow (Q rest : r  = 0.89, mean bias = 2.52; SD = 15.47), hyperemic flow (Q hyper : r  = 0.88, mean bias = −2.65; SD = 27.96), resting microvascular resistance (R μ ‐ rest : r  = 0.90, mean bias = 52.14; SD = 228.29), hyperemic microvascular resistance R μ ‐ hyper : r  = 0.92, mean bias = 12.95; SD = 57.80), and MRR (MRR: r  = 0.89, mean bias = 0.04, SD = 0.59).  Procedural time was significantly shorter with the automated method (5′25″ ± 1′23″ vs. 4′36″ ± 0′33″, p  = 0.013). Conclusion: Continuous intracoronary thermodilution‐derived measurements of absolute flow, absolute resistance, and MRR can be fully automated. This further shortens and simplifies the procedure when performing paired resting‐hyperemic measurements.